Peran Lembaga Adat Gampong Dalam Penyelesaian Sengketa - Haikal, Muhammad (Yayasan Madinah Al-Aziziyah, 2024)
Aceh is a unique province with its special characteristics, including the Qanun that regulates village judiciary. However, does the village customary institution play a role in dispute resolution, and what is its legal basis? This research aims to examine the legal basis and the role of the village customary institution in Aceh in dispute resolution. The method used is qualitative. The research results show that the village customary institution has a significant and important role in dispute resolution, and its legal basis is Qanun Number 9 of 2008, which outlines the procedures and structure of the customary court apparatus.